Assessment of Potential Drug-Drug Interactions and its Associated Factors in Medical Intensive Care Unit of a Tertiary Care Hospital in Nepal - Upreti, Anup Raj; Shrestha, D; Thapa, S; Lingden, BK (Nepal Medical College Journal, 2020)
Drug interaction may cause an increase in the toxicity of a drug, increases the likelihood of adverse drug reactions, or cause a reduction in the efficacy of particular drug therapy, which may worsen the patient’s condition directly or indirectly. This study aims to assess the potential drug-drug interactions (pDDIs) and their associated factors in the Medical Intensive Care Unit (MICU). We carried out a descriptive retrospective study based on the hospital records of 100 MICU patients. Micromedex Interaction application, designed by Truven Health Analytics Inc., was used to screen prescribed medications. We found 219 drug interactions out of 856 drugs prescribed. The average number of drug interactions per patient was 2.19. The frequency of drugs prescribed, the number of days in MICU, and age had a positive correlation with the occurrence of pDDIs. There were 44.7% major pDDIs; pharmacodynamic being the commonest mechanism for it. Most patients in MICU were at the risk of developing pDDIs. A substantial number of interactions had a major severity. Therefore, there is a need for active surveillance for pDDIs to prevent patient harm during particular drug therapy.